2010
DOI: 10.1097/brs.0b013e3181ce873d
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study and Multivariate Analysis of the Incidence of C5 Palsy After Cervical Laminoplasty

Abstract: This study showed significant evidence indicating the higher risk of postoperative C5 palsy in open-door LP than double-door LP. Because OPLL as well as open-door LP were recognized as the risk factors of C5 palsy, asymmetric decompression by open-door LP might introduce imbalanced rotational movement of spinal cord and result in C5 palsy. We recommend double-door LP to minimize the postoperative C5 palsy, in particularly, if the patient has OPLL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
3
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 20 publications
4
62
3
4
Order By: Relevance
“…The degree of PPDCP and PADCP was graded in our study using the manual muscle test (graded from 0 to 5, with 0 as no movement and power and 5 with normal strength). The PPDCP in five of the studied cases was grade 0 (2 immediately and 3 over one week period), 3 were grade 1 and 2 were grade 2. cervical decompression for CSM has been reported to average 4.6% (range 0%-30%) [7][8][9]11,13,14]. The incidence of C5 palsy in this study is comparable at 20%.…”
Section: Clinical Datasupporting
confidence: 49%
See 2 more Smart Citations
“…The degree of PPDCP and PADCP was graded in our study using the manual muscle test (graded from 0 to 5, with 0 as no movement and power and 5 with normal strength). The PPDCP in five of the studied cases was grade 0 (2 immediately and 3 over one week period), 3 were grade 1 and 2 were grade 2. cervical decompression for CSM has been reported to average 4.6% (range 0%-30%) [7][8][9]11,13,14]. The incidence of C5 palsy in this study is comparable at 20%.…”
Section: Clinical Datasupporting
confidence: 49%
“…It has also been reported after other posterior-based techniques. The incidence varies from 0-50% depending on the technique used, how the condition is defined and which patient group is being analysed [3,[4][5][6][7][8]9,10]. Takemitsu et al [11] reported a higher incidence among patients undergoing instrumentation than those treated by laminoplasty alone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risks unique to laminaplasty include premature lamina closure after open-door technique with resultant re-stenosis [33] and axial neck pain [40]. Cervical nerve root palsy (most commonly C5 palsy) remains a risk predominantly of posterior cervical decompression [29] but has also been reported to occur following anterior decompression [22].…”
Section: Complications Of Surgerymentioning
confidence: 99%
“…Kaneyama et al [18] reported that asymmetric decompression by open-door laminoplasty may introduce imbalanced rotational movement of the spinal cord and result in C5 palsy. In this study, simulated corpectomy using axial scanned images in the ER-position showed that the width of corpectomy was directed to the right.…”
Section: Discussionmentioning
confidence: 99%